Comparing corneal biomechanical parameters between primary open-angle glaucoma and pseudoexfoliation glaucoma using corvis ST - Ali Azimi; Mostafa Nazarpour Servak; M. Hossein Nowroozzadeh; Hooman Razmi; Amir Mohammad Fathian; Faranak Nasiri Shirazi; Seyed Mehdi Tabatabaei (BMC Ophthalmology)
Abstract Background To compare corneal biomechanical properties between primary open-angle glaucoma (POAG) and pseudoexfoliation glaucoma (PXG) using CorVis ST. Methods Thirty-three eyes of 33 patients with PXG and 29 eyes of 29 patients with POAG were enrolled in this cross-sectional study. All eyes underwent CorVis ST. Biomechanical parameters at the first and second applanation and highest concavity were measured. Man-Whitney U test and stepwise linear regression were used to compare the parameters between groups. Results The mean age was 67.1 ± 7.9 and 70.3 ± 7.1 years in the POAG and PXG groups, respectively (P = 0.072). Eighteen patients in each group were male (P = 0.549). Intraocular pressure (IOP) measured by Goldmann applanation tonometry was not different between groups (P = 0.112) while the PXG group had higher biomechanically corrected IOP (14.3 ± 3.5 mmHg vs. 15.9 ± 3.4 mmHg; P = 0.042). Central corneal thickness was lower in the PXG group (546 ± 29 μm vs. 523 ± 37 μm; P = 0.008). A2 velocity was lower in the PXG group (P = 0.008). The highest concavity (HC) deformation amplitude and deflection length and peak distance were lower in the PXG group (p < 0.05). The PXG eyes had a higher stress-strain index (1.29 ± 0.26 vs. 1.42 ± 0.27; P = 0.022). Conclusion The results of the current investigation are in favor of the presence of a stiffer cornea in the PXG group.